Technological and Organizational Change and the Careers of Workers - Michele Battisti; Christian Dustmann; Uta Schönberg (Institute of Labor Economics (IZA), 2022)
This paper investigates the effects of technological and organizational change (T&O) on jobs and workers. We show that although T&O reduces firm demand for routine relative to abstract task-based jobs, affected workers do not face higher probability of non-employment or lower earnings growth than unaffected workers. Rather, firms that adopt T&O offer routine workers re-training opportunities to upgrade to more abstract jobs. Older workers form an important exception: T&O increases the risk that they permanently withdraw from the labor market and reduces their earnings, regardless of the tasks they performed in the firm prior to T&O.
Keywords: J23; J24; O33; 330; careers of workers; technological change